Green Finance di Indonesia: Tinjauan Umum - Andi Yunus; Muammar khadafi (Management Studies and Business journal, 2024)
This research uses the Volz legal instrument framework to analyze the legal aspects of Green Finance in Indonesia. The results of this research find that Bank Indonesia and the Financial Services Authority have regulatory tools to influence loans, loan policies and investment choices. There are various green finance instruments available under Indonesian law, including loan-to-value/finance-to-value ratios, environmentally friendly financial guidelines, and affirmative steps. The legal framework for environmentally friendly finance in Indonesia is quite promising, with the implementation of sustainable finance by the business world and government support. However, there is room for Bank Indonesia to adopt additional regulatory instruments to further encourage sustainable finance